2022
DOI: 10.1038/s41598-022-05023-2
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomized study, use of closed suction drainage after revision hip arthroplasty may lead to excessive blood loss

Abstract: Suction drainage after primary total hip arthroplasties (THA) offers no benefits. Revision hip arthroplasties (RHA) are more demanding procedures and associated with greater blood loss compared to primary cases. There is still a lack of literature regarding the application of drainage in RHA. A total of 40 patients who underwent RHA were included in this prospective study. Simple randomization with an allocation ratio 1:1 was performed. Primary outcomes: total blood loss, hemoglobin drop, joint hematoma size i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…A heterogeneous meta-analysis reported that compared with regular drainage, autotransfusion reduced the need for allogeneic transfusion following TKA and THA, but not when compared with autotransfusion with no drainage 507 . Postoperative closed-suction drainage was found to increase total blood loss and blood transfusion requirements in THA 508,509 and provided no benefit in revision THA, as postoperative blood loss, transfusion rate and length of hospital stay may be higher with its use 510,511 . A recent prospective controlled double-blind study demonstrated that drainage of surgical wounds following primary THA might cause an increased requirement for blood transfusion 512 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A heterogeneous meta-analysis reported that compared with regular drainage, autotransfusion reduced the need for allogeneic transfusion following TKA and THA, but not when compared with autotransfusion with no drainage 507 . Postoperative closed-suction drainage was found to increase total blood loss and blood transfusion requirements in THA 508,509 and provided no benefit in revision THA, as postoperative blood loss, transfusion rate and length of hospital stay may be higher with its use 510,511 . A recent prospective controlled double-blind study demonstrated that drainage of surgical wounds following primary THA might cause an increased requirement for blood transfusion 512 .…”
Section: Discussionmentioning
confidence: 99%
“…507 Postoperative closed-suction drainage was found to increase total blood loss and blood transfusion requirements in THA 508,509 and provided no benefit in revision THA, as postoperative blood loss, transfusion rate and length of hospital stay may be higher with its use. 510,511 A recent prospective controlled double-blind study demonstrated that drainage of surgical wounds following primary THA might cause an increased requirement for blood transfusion. 512 A meta-analysis in posterior spinal surgery with limited quality of evidence revealed no significant differences regarding estimated blood loss between patients using closed-suction drainages.…”
Section: Drainagementioning
confidence: 99%
“…In a recent study, however, researchers found that the use of suction drainage after RHA may lead to higher blood loss in the early postoperative period. (See Bartosz et al, 2022. )…”
mentioning
confidence: 99%